Meeting the Universe Halfway. Feminist debate and Actor-Network Theory - Restituta Castiello (Tecnoscienza – Italian Journal of Science & Technology Studies, 2010)
Starting from Karen Barad’s volume Meeting the Universe Halfway, Quantum Physics and the Entanglement of Matter and Meaning, I intend to focus on some points of convergence and divergence between two different debates on STS: the feminist approach and the Actor-Network Theory. This paper starts from the assumption that the growing interest in ontology and realism, and the switch from a representationalist paradigm to a performative one, are more or less explicitly influenced, in both debates, by Jilles Deleuze’s philosophy, with particular regard to his approach to reality as becoming. I eventually focus on how feminist STS and ANT have interpreted this opening to a more complex concept of reality, also taking into account the implications, even political ones, of these two different epistemological approaches.